Association studies of the BDNF and the NTRK2 gene polymorphisms with prophylactic lithium response in bipolar patients. (November 2008) - Dmitrzak-Weglarz, Monika; Rybakowski, Janusz K; Suwalska, Aleksandra; Skibinska, Maria; Leszczynska-Rodziewicz, Anna; Szczepankiewicz, Aleksandra; Hauser, Joanna
The neuroplasticity hypothesis of bipolar disorder indicates that the BDNF/Trk signaling pathway is associated with the pathogenesis of this illness and treatment with mood stabilizers, such as lithium. This paper describes a relationship between response to lithium prophylaxis and polymorphisms of two functionally connected genes: BDNF and NTRK2, in bipolar illness. Analyses of four SNPs of the BDNF gene (rs2030324, rs988748, rs6265 [Val66Met]and rs2203877) and three of the NTRK2 gene (rs1187326, rs2289656, rs1187327) were performed in the 108 bipolar patients, classified as excellent responders (23%), partial responders (51%) and nonresponders (26%) to lithium. An association of C/G (rs988748) and G/A (rs6265) polymorphisms of the BDNF gene with a degree of prophylactic lithium response were found. No association with lithium response was revealed with the polymorphism of NTRK2 gene, neither with interaction of BDNF and NTRK2 genes.